Successful support of biventricular heart failure patients by new EXCOR® Adult pumps with bileaflet valves: a prospective study - Schmack, Bastian; Weymann, Alexander; Ruschitzka, Frank; Autschbach, Rüdiger; Raake, Philip; Jurrmann, Nadine; Menon, Ares Krishna; Karck, Matthias; Wilhelm, Markus J.; Ruhparwar, Arjang (Clinical research in cardiology, 2018)
The Berlin Heart EXCOR® Adult biventricular assist device (BiVAD) is an approved mechanical circulatory support for patients with end-stage biventricular heart failure. In this prospective post-market clinical follow-up study, we present the first clinical experience of the new EXCOR® Adult pump with bileaflet (BL) valves in Europe.
Published online: 2 January 2018
Gesehen am 23.03.2020